Bahan Bahan Ajar Digital Berbasis Website Kodular terhadap Civic Knowledge Peserta Didik Materi Kebangkitan Nasional dan Sumpah Pemuda - Gaisani Umu Mudhiah; Aim Abdulkarim; Prayoga Bestari (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2025)
The integration of digital technology in Civic Education learning is still limited to the distribution of materials, while the need for interactive teaching materials is increasingly urgent. Kodular, a website-based digital teaching material creation platform without programming skills, offers an innovative solution to increase student engagement and understanding. This study aims to analyze the effect of using Kodular website-based digital teaching materials on improving civic knowledge on the National Awakening and Youth Pledge materials at SMP Negeri 29 Bandung. The method used is a quasi-experimental method with two groups, namely the experimental group using Kodular website-based teaching materials and the control group with conventional teaching materials. The sample consisted of students in grades VIII G and VIII H, with pre-test, post-test, and satisfaction questionnaire instruments. The results show that Kodular website-based teaching materials significantly improve student understanding compared to conventional teaching materials. These findings support the development of innovative digital teaching materials to improve the quality of Civic Education learning.